Real-world data of HER2-low metastatic breast cancer: A population based cohort study. (December 2022) - Holthuis, Emily I.; Vondeling, Gerard T.; Kuiper, Josephina G.; Dezentjé, Vincent; Rosenlund, Mats; Overbeek, Jetty A.; van Deurzen, Carolien H.M.
Abstract: Background: With the introduction of investigational human epidermal growth factor receptor 2 (HER2) targeting treatments, thorough understanding of breast cancer with different HER2 expression levels is critical. The aim of this study was to compare clinicopathologic characteristics and survival of patients with metastatic breast cancer according to the level of HER2 expression. Methods: Women with distant metastatic breast cancer during 2008–2016 were selected from PALGA, the Dutch Pathology Registry, and linked to the PHARMO Database Network. Breast cancer samples were categorised as HER2 immunohistochemistry score 0 (IHC0), HER2-low or HER2+. Results: Among women with hormone receptor (HR) positive metastatic breast cancer (n = 989), 373 (38%) cancers were HER2 IHC0, 472 (48%) were HER2-low and 144 (15%) were HER2+. Among HR negative patients (n = 272), the proportion of HER2 IHC0, HER2-low and HER2+ was 110 (40%), 104 (38%) and 58 (21%) respectively. Within the HR + cohort, patients with HER2 IHC0 or HER2-low cancer were significantly older compared to HER2+ patients. This age difference was not seen in the HR-cohort. The localisation of distant metastases differed significantly between HER2 IHC0 or HER2-low versus HER2+ cases. Survival rates did not differ markedly by subtypes. Conclusion: Substantial proportion of patients had a HER2-low breast cancer. No clear differences in survival were found when comparing HER2 and HR status. Getting more granular insights in the level of HER2 expression and addressing HER2-low as a separate category could help to assess the impact of emerging treatment strategies. Therefore, more detailed information on HER2 expression should be routinely reported. Highlights: A substantial proportion of patients had HER2-low breast cancer. HER2 expression levels differed between the primary tumour and the metastases. It is important to assess HER2 status in both the primary tumour and metastases. Similar survival in HER2-low and HER2-0 BC patients, stratified for HR.